Design and Microfabrication Considerations for Reliable Flexible Intracortical Implants - Sohal, Harbaljit S.; Vassilevski, Konstantin; Jackson, Andrew; Baker, Stuart N.; O’Neill, Anthony (Frontiers in Mechanical Engineering, 2016)
Current microelectrodes designed to record chronic neural activity suffer from recording instabilities due to the modulus mismatch between the electrode materials and the brain. We sought to address this by microfabricating a novel flexible neural probe. Our probe was fabricated from parylene-C with a WTi metal, using contact photolithography and reactive ion etching, with three design features to address this modulus mismatch: a sinusoidal shaft, a rounded tip and a polyimide anchoring ball. The anchor restricts movement of the electrode recording sites and the shaft accommodates the brain motion. We successfully patterned thick metal and parylene-C layers, with a reliable device release process leading to high functional yield. This novel reliably microfabricated probe can record stable neural activity for up to two years without delamination, surpassing the current state-of-the-art intracortical probes. This challenges recent concerns that have been raised over the long-term reliability of chronic implants when Parylene-C is used as an insulator, for both research and human applications The microfabrication and design considerations provided in this manuscript may aid future development of flexible devices for biomedical applications.